Teaching Elementary Economics Using Children's Literature - Julia Mittelberg (The Advocate, 2013)
Teaching economics to elementary aged children can be a challenge for classroom teachers. Using popular children’s literature is an engaging and fun way to involve students in learning important economic lessons while integrating the content with language arts standards. This article will describe how to use children’s books to teach economic ideas and it provides the reader with numerous examples of popular literature that can be employed to effectively teach concepts like opportunity cost, scarcity, and resources. Additionally, recommendations for using the books and how to find appropriate texts by grade level using existing on-line databases are included. Teaching economic concepts in elementary classrooms is a task that teachers may find intimidating due to common misconceptions about economics. Teachers may think of economics on a national or global scale, dealing with large amounts of money, numbers, and complicated mathematical processes, however the reality of what should be taught in elementary is very different from this. When conceptualizing economics in terms of college level economics or the newscaster’s reports on the nation’s economic state teachers might wonder, “How can I possibly explain these ideas to my 3rd graders?” First, teachers must look at the social studies standards set by their state to really understand what is expected at each grade level. The content is not difficult for students to understand if teachers are able to make the concepts more concrete and applicable to the personal lives of their students. As Dr. Yana van der Meulen Rodgers from Rutgers University states in Newman’s (2010) article: “Decades of research in economics, education, and early-childhood development have shown that young children enter the primary grades with an experience-based knowledge of economics and that they are quite capable of learning basic economics during the primary grades (para. 1).” This should be encouraging for teachers as they strive to connect economic content to the lives of young children. One way to make this link is through the use of children’s literature to teach economic concepts. Many teachers have a routine in place of reading literature aloud to students, so it is an easy transition to move from making literacy-based connections such as phonics, vocabulary, character studies, or context clues alone to also include content connections to social studies concepts like economics (Newman, 2010). The key is for the teacher to begin to look at books through an interdisciplinary lens. Some books have an obvious connection to economics, while others may not be as apparent. The purpose of this article is to provide some examples of literature that can be used to teach a variety of economic concepts to elementary students in order to engage young learners in meaningful learning.